1079 USE OF AN ADVANCE CARE PLAN CHECKLIST TO IMPROVE COMMUNICATION AND ASSESSMENT OF THE IMPACT ON HOSPITAL READMISSIONS. (14th June 2022) - Adams, G; Woodcock, J; Barradell, V; Pennells, D; Narramore, R
Abstract: Introduction: Advance care planning (ACP) is a vital part of holistic and person-centred care. It allows formalising of an individual's wishes and best interests, and avoids unnecessary or unwanted interventions including, potentially, hospital admissions. It is crucial that any decisions or recommendations are communicated to all relevant healthcare professionals to ensure peoples' wishes are upheld. We developed this project to review and improve documentation and communication on discharge when a decision had been made to limit care to the community and avoid admission. Method: A checklist was developed comprising 11 criteria to be documented in the discharge letter and actions to disseminate information including; updating the ReSPECT form and alerting the hospital frailty and community out of hours teams. We carried out a closed loop audit of patients where admission should be avoided and reviewed discharge letters against the criteria. Where patients were readmitted we reviewed the notes to determine whether the admission was appropriate. Results: We compared patients discharged between February 2020–February 2021 and then from March–September 2021. 161 and 27 patients were identified respectively. Average age was 84.6 and 87.3 years respectively. In cohort 2 48.1% of patients were readmitted, up from 8.7% during the previous cycle. 33% of admissions in cohort 2 and 38.9% of readmissions in cohort 1 were deemed appropriate. Documentation improved in 10 of the 11 criteria. Average length of stay for readmissions was reduced from 16.7 to 5.7 days. Conclusion: As evidenced by our study utilising a checklist has improved documentation and dissemination of ACPs to the Community. This did not lead to a reduction in hospital admissions but this may have been skewed by factors relating to the Covid-19 pandemic. We did find a significant reduction in length of stay for those subsequently readmitted.